Norms and international standards related to reduce risk management: a literature review - Fuentes, César (2011)
The current work aims to develop a revision of the literature within the main concepts in the international rules and standards related to risk management in companies. By this way, there will be an analysis of issues such as the COSO - ERM model, an introduction to the ISO 27000 and 31000 standards; and the Project Management according to PMI targeted at risk management.